Serum Methylarginines and Hearing Loss in a Population-based Cohort of Older Adults. Issue 4 (April 2018) - McEvoy, Mark; Harris, David C.; Mangoni, Arduino A.; Sarant, Julia Z.
Abstract : Objective: Age-related hearing loss is associated with endothelial dysfunction and increased cardiovascular risk, suggesting a vascular etiology. Methylarginines are endogenous nitric oxide synthase inhibitors that cause endothelial dysfunction and increase cardiovascular disease risk. This study is the first to examine the hypothesis that higher serum concentrations of methylarginines are associated with greater hearing loss prevalence. Study Design/Patients: Cross-sectional audiometric data on hearing levels, and serum methylarginines were collected from a population-based sample of 630 older community-dwelling adults. Results: Linear regression analysis showed a statistically significant association between higher serum concentrations of asymmetric dimethylarginine (ADMA) and L-arginine and greater degrees of hearing loss for males, particularly over 75 years. Higher body mass index and previous history of stroke were also associated with hearing loss. For females, ADMA concentration was not associated with hearing loss, but higher serum L-arginine concentrations were associated with reduced hearing loss prevalence in older females. Antihypertensive medication use was also associated with reduced hearing loss prevalence. LDL cholesterol and previous myocardial infarction were associated with greater hearing loss. Conclusion: This study showed a significant association between serum concentrations of ADMA and hearing loss for males, consistent with the association between endothelial dysfunction and hearing loss. The opposite effect of L-arginine on hearing loss in males versus females might reflect a different role of this precursor toward nitric oxide versus methylated arginines synthesis. These findings are potentially clinically significant if the association between ADMA and hearing loss is causal, as serum methylarginine levels are modifiable through pharmacotherapeutic/lifestyle interventions.